Compensation - Milkovich, George T.
Compensation, 10th Edition, by Milkovich, Newman and Gerhart is the market-leading text in this course area. It offers instructors current research material, in depth discussion of topics, integration of Internet coverage, excellent pedagogy, and a truly engaging writing style. The authors consult with leading businesses, have won teaching awards, and publish in the leading journals. This text examines the strategic choices in managing total compensation. The total compensation model introduced in chapter one serves as an integrating framework throughout the book. The authors discuss major compensation issues in the context of current theory, research, and real-business practices. Milkovich, Newman and Gerhart strive to differentiate between beliefs and opinions from facts and scholarly research